Les Services sociaux vs les lesbiennes et les gais du Québec : un dossier noir - Rassemblement national des lesbiennes et gais du Québec. (Le RNLGQ, 1979)
Keywords: 1900-1999; 1970-1979; amériques; corps; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; québec; régions géographiques; santé; thématiques; violences

Georgie - Jutras, Jeanne-d'Arc (Pleine Lune, 1978)
Georgie vit son enfance dans un quartier défavorisé du Montréal des années cinquante. Elle apprend au fil des ans le prix à payer pour vivre son lesbianisme dans un monde clos où les sermons religieux n’empêchent ni la misère ni la faim. Georgie a la tendresse et la violence de celles qui savent qu’il leur faudra tout arracher à la vie, que rien jamais ne leur sera donné. Elle avance et vit sans compromis.Georgie est écrit comme un coup de poing sur la table, avec l’éloquence cinglante des gens patients, quand ils en ont ras le bol.Gilles Cossette, Lettres québécoises.
Keywords: 1900-1999; 1950-1959; amériques; personnes lesbiennes; périodes historiques; québec; roman; régions géographiques; sexualité; thématiques; violences

The Destruction of American Indian families - Unger, Steven (Association on American Indian Affairs, 1977)
Responding to the need for a comprehensive source of information regarding the separation of American Indian children from their families, this book presents essays which: examine the Indian child-welfare crisis in contemporary, legal, and historical perspectives; document the human cost of the crisis to Indian parents, children, and communities; and report on innovative programs designed and implemented by the Indian tribes themselves. Specifically, this book includes the following sections and essay titles: (1) Contemporary Overviews ("The Destruction of American Indian Families" and "The Role of the Federal Government: A Congressional View"); (2) Historical Perspectives ("The Effects of Boarding Schools on Indian Family Life: 1928" and "'Kid Catching' on the Navajo Reservation: 1920"); (3) The Human Cost ("'The Drunken Indian': Myths and Realities"; "The Wasted Strengths of Indian Families", "The Human Cost of Removing Indian Children from Their Families", "Child-Welfare Services to Indian People in the Albuquerque Area", "Indian Child Welfare in Oregon", "The Ravage of Indian Families in Crisis", "The Question of Best Interest", and "The Placement of American Indian Children–The Need for Change"); (4) A Legal Perspective ("Parent and Child Relationships in Law and in Navajo Custom"); (5) Tribal Actions ("Indian Children and Tribal Group Homes: New Interpretations of the Whipper Man" and "Tribal Resolutions"). (JC)
Keywords: american indian families; amériques; approches et analyses; autochtones; cours; discipline; droit; famille; his4443; histoire et politique; premier cycle; racisme; racisme systémique; residential schools; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violence systémique; violences; états-unis